EU Wine Exporters Competing in Changing International Markets - Roberto Henke; Anna Carbone (World, 2025)
Wine markets have deeply changed in recent decades in many regards. In particular, wine trade patterns have been deeply reshaped, and this also affects traditional EU exporters, who operate in a more competitive environment, with new players challenging their position and forcing them to readjust their strategies. This study analyzes recent trends in the wine exports of major EU producers. Its goal is to contribute to assessing to what extent their positioning in the international wine markets differs, and to understand the kind of competition they engage in within destination markets, with a focus on the role of their export quality as a major competitive advantage. This analysis only looks at bottled wines, both still and sparkling. It combines the use of traditional trade indicators—such as export quotas, penetration rates, and the average unit value of exports (AUV) with an innovative indicator, called C-Consy, aimed at measuring the sophistication levels of the destination markets. The results show that EU competitors behave in different ways and move along different paths. Some of them show an increasing ability to sell their products in higher segments of sophisticated markets. Others are also quite well positioned in the global arena, but they are fighting to fully catch up with the increasing demand for more sophisticated products from their clients. Some have managed to improve quality and hence advance to higher market segments, while others have shown greater weakness in facing global competition. Looking at typologies, exporters do not always show the same positioning and trends for still and sparkling wines.